Starch Based Nanogels: From Synthesis to Miscellaneous Applications - Saracoglu, Pelin; Ozmen, Mehmet Murat (WILEY-V C H VERLAG GMBH, 2021)
Nanogels are nanosized three-dimensional polymeric networks that are able to swell in a solvent. They are of great interest due to their high surface area, response to environmental stimuli, and high loading efficiency. In recent years, nanogels prepared from polysaccharides have captured broad attention because of their superior biocompatibility, easy gelation, and functionalization. In particular, starch based nanogels (SBNs) are promising nanomaterials for versatile applications including biomedical, food and pharmaceutical industries. Despite a high number of publications for other polysaccharide nanogels, a limited number of SBNs research articles are available in the literature. This review provides a brief summary of previous studies on the synthesis and applications of SBNs. Their current status is specified briefly covering the last decade. Some studies reveal that starch type, gelation time, and amylose/amylopectin ratio are critical parameters during SBNs synthesis. Numerous starch derivatives and combinations of starch with various polymers can facilitate their synthesis with desired features. Importantly, in vivo biodegradability and biocompatibility investigations are required to extend SBNs usage in the biomedical field including drug and peptide delivery. The overview provided by this review will offer a valuable understanding and insight to help direct the design and uses of SBNs.
Keywords: carbohydrate; crosslinking; nanocarrier; nanogel; starch; Food Science & Technology